1979
DOI: 10.1103/physrevlett.43.1005
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Resonance-Enhanced Nuclear-Motion Effects in Molecular Photoionization

Abstract: Shape resonances in molecular photoionization are shown to induce strong coupling between vibrational and electronic motion over a spectral range several times broader than the resonances half-width. This coupling is manifested by large deviations from Franck-Condon intensity distributions and strong dependence of photoelectron angular distributions on the vibrational state of the residual ion. These effects are illustrated for the 3a g photoionization channel of N 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
1
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(120 citation statements)
references
References 30 publications
(4 reference statements)
10
108
1
1
Order By: Relevance
“…Earlier publications have shown that shape resonances can lead to a strong modulation of the ionization cross sections depending on intranuclear distances and hence the vibrational distributions; see, e.g., Ref. 39. These modulations were seen in states that could couple to ionic states with high l values.…”
Section: A Photon Energy Dependence Of the Electron Spectramentioning
confidence: 86%
“…Earlier publications have shown that shape resonances can lead to a strong modulation of the ionization cross sections depending on intranuclear distances and hence the vibrational distributions; see, e.g., Ref. 39. These modulations were seen in states that could couple to ionic states with high l values.…”
Section: A Photon Energy Dependence Of the Electron Spectramentioning
confidence: 86%
“…Thus, it possible to compare the rotational substructure between the two bands as a function of incident photon energy, analogous to a previous study on vibrationalrotational-electronic ͑V-R-E͒ correlations in 2 u Ϫ1 photoionization of N 2 . 37 It is well known that the effects of shape resonances are influenced by the bond length for diatomic systems, 69,70 so it is reasonable to inquire if the rotational substructure would be affected, particularly in the lower energy region where the shape resonant effects are dominant. This comparison has been generated, and the results are shown in Fig.…”
Section: A Typical Comentioning
confidence: 99%
“…39 In the case of neutral diatomic molecules, dramatic changes in the PAD have been observed between different vibronic photoionization bands of N 2 , CO, and O 2 . [40][41][42] Such effects are associated with strong coupling of the electronic and vibrational motion and usually a breakdown of the Born-Oppenheimer approximation as a consequence of excitation of intermediate, autoionizing Rydberg states or shape resonances. 42 It is well known that the PAD is dependent on electron kinetic energy ͑E͒.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Such effects are associated with strong coupling of the electronic and vibrational motion and usually a breakdown of the Born-Oppenheimer approximation as a consequence of excitation of intermediate, autoionizing Rydberg states or shape resonances. 42 It is well known that the PAD is dependent on electron kinetic energy ͑E͒. 43 To separate the effect of vibrational excitation from the E dependence, one must, ideally, compare transitions that terminate in different vibrational states but correspond to the same E. This approach requires experiments at multiple, carefully selected photoexcitation wavelengths.…”
Section: Introductionmentioning
confidence: 99%